Britain and Germany in the twentieth century - Görtemaker, Manfred (German historical perspectives series, 2006)
Preface by Timothy Garton Ash and Gerhard A. Ritter. The history of British-German relations in the twentieth century has been characterized by a remarkable dichotomy of friendship and hostility. What started as a family affair with Kaiser Wilhelm II, the grandson of Queen Victoria, and his admiration for the British Navy, soon turned into a violent struggle for superiority in Europe during two World Wars. After 1945 the two countries became allies, if not friends, again. But when Germany was reunified in 1990, Prime Minister Thatcher did not hesitate to warn that history might repeat itself, referring to the creation of the German Reich in 1871 as the starting-point of the European tragedy. This book considers the most critical aspects of this volatile relationship during the past 100 years: the rivalry at sea before World War I, David Lloyd George and the Weimar Republic, the appeasement policy of the 1930s and Rudolf Hess's flight to Scotland in 1941, the post-World War II period of occupation and partnership, and the British attitude toward the new Germany post-1990.
Includes bibliographical references and index
Keywords: Great Britain -- Foreign relations -- Germany; Great Britain -- Foreign relations -- 20th century; Germany -- Foreign relations -- Great Britain; Germany -- Foreign relations -- 20th century; Aufsatzsammlung; Geschichte 1900-2000; Deutschland; Außenpolitik; Großbritannien